An international public partnership for genetic enhancement of cowpea using a holistic approach to biotechnology - Ortíz, R. (2003)
Cowpea is the most important product in African dryland agriculture. Its protein-rich grains are the main product of the crop, which are commonly eaten in different forms by rural and urban peoples. African farmers growing cowpea in their fields often harvest low yields because many biotic and abiotic factors affect the crop. Cultural practices, together with genetic manipulation through breeding (including biotechnology), can ameliorate yield-limiting factors affecting the farming of cowpea in Africa. Genetic transformation and DNA marker-aided selection are two of the most important methods expected to be used in the next decade by cowpea breeders.